Congenital tuberculosis at the Dos de Mayo hospital in Lima Peru - Fernández, Alejandro (1995)
A case of congenital tuberculosis with fatal outcome is presented. Tuberculosis lesions of the mother's genital tract by endometrial biopsy and hysterosalpingography were shown. The preterm newborn had thirty sixth weeks of pregnancy and weighed 2760 g. After an evolution that included hyperbilirrubinemia, hydrocele, equinus varus, abdominal rectus diastasis, pyodermitis and omphalitis, the infant developed respiratory failure with cyanosis on day 27. Diagnosis was milliary tuberculosis and sepsis with fatal outcome. This case meets Cantwell's proposal for diagnostic criteria for congenital tuberculosis, as tuberculosis was documented in the newborn and in the mother's genital tract, confirmed by anatomopathological examination. Postnatal transmission was excluded by isolation of the newborn from the mother and the presence of lesions from the very first weeks of life.